STRATEGI KOMUNIKASI DINAS KB UNTUK PERUBAHAN PERILAKU IBU HAMIL DALAM PERCEPATAN PENURUNAN STUNTING DI KELURAHAN PENAJAM KABUPATEN PENAJAM PASER UTARA - Linda Sari; Nur Alim Djalil; Andi Nur Insan (PIRSAP (Paser Institute for Scientific Research and Publications), 2025)
This study aims to analyze the communication strategy of Dinas KB in changing the behavior of pregnant women to accelerate stunting reduction in Penajam Village, Penajam Paser Utara Regency. In addition, this study also analyzes the implementation of the communication strategy applied, including the supporting and inhibiting factors that affect the effectiveness of the program. This research was conducted in Penajam Village, Penajam Paser Utara Regency, using qualitative methods and a phenomenological approach. This approach is used to deeply understand individual experiences related to the communication strategies applied. Data were collected through in-depth interviews, participatory observation, documentation, and triangulation to obtain accurate and comprehensive information. The results showed that Dinas KB's communication strategy has been implemented through counseling at Posyandu, home visits by family planning cadres and the Family Support Team (TPK), and the utilization of social and print media. The main obstacles in implementing this strategy are low public awareness, the circulation of nutrition-related myths, and economic limitations that affect access to nutritious food. Supporting factors for the success of the program include cross-sectoral cooperation, the use of social media, as well as family support and government assistance. To improve the effectiveness of this communication strategy, it is necessary to intensify education, optimize the use of digital media, and increase coordination between related agencies to support the acceleration of stunting reduction more optimally.